Long-term effects of access to health care: Medical missions in colonial India - Calvi, Rossella; Mantovanelli, Federico G. (Journal of development economics, 2018)
Health outcomes in India vary substantially across regions. Motivated by mounting evidence of the historical persistence of institutions and behavior, this paper studies the historical origins of this health variation. We examine the long-term consequences of the Protestant medical missionary enterprise that spread throughout India in the nineteenth century. Protestant mission medicine sought to place itself within non-European social and institutional milieus, contributing to the diffusion of Western medicine among the local population. We construct a novel fully geocoded dataset that combines contemporary individual-level data with historical information on missionary activities. We document a robust positive association between proximity to a Protestant medical mission and current individuals' health outcomes. Our analysis indicates that this long-run link is not driven by religious conversion or persistence of infrastructure, but possibly by improvements in individuals' health potential and changes in hygiene and health habits. •We study the long-term health impact of Protestant medical missions in colonial India.•A novel fully-geocoded dataset combines current health outcomes with historical data.•Proximity to a Protestant medical mission strongly predicts individual health today.•This long-run link is not driven by conversion or persistence of infrastructure.•Changes in health practices, knowledge, and maternal care are the primary mechanisms.